Doctor shopping for medications used in the treatment of attention deficit hyperactivity disorder: shoppers often pay in cash and cross state lines. (May 2015) - Cepeda, M. Soledad; Fife, Daniel; Berwaerts, Joris; Friedman, Andrew; Yuan, Yingli; Mastrogiovanni, Greg
Abstract Background: Doctor shopping, defined by filling overlapping prescriptions from more than one prescriber at more than two pharmacies, is a way to obtain scheduled medications for diversion or abuse. Little is known about how far attention deficit hyperactivity disorder (ADHD) medication shoppers travel, how often they cross state lines to fill their ADHD prescriptions and how often they pay for their medication in cash, i.e. entirely out of pocket. Objective: We sought to describe the pattern of doctor shopping for ADHD medications: how far shoppers travel, how often they cross state lines to fill their prescriptions, and how often they pay in cash. Methods: Retrospective cohort study using LRx, a large US retail prescription database. We included subjects with any ADHD medication dispensed between 2011 and 2012. Subjects were followed for 18 months. Results: Of a total of 4 402 464 subjects exposed to ADHD medications, 0.4% developed shopping behavior. Women were more likely to become shoppers. Shoppers travelled a median of 91.9 miles and non-shoppers 0.2 miles to fill their ADHD prescriptions. Almost 28% of the shoppers filled prescriptions in >1 state compared with 4.3% of non-shoppers. Of the shoppers, 27.3% paid at least one prescription in cash compared to 14.4% of the non-shoppers. Conclusions: Shoppers travelled larger distances, visited more states and paid in cash for ADHD medications more often than non-shoppers. Data sharing among prescriptions monitoring programs can improve their effectiveness and drug utilization studies should take account of cash purchases.